THE EFFECT PERCEIVED DESIGN QUALITY, PERCEIVED CAPABILITY OF ORDER, REPUTATION, TRUST AND PRICE TO REPURCHASE INTENTION LANDSCAPE ON PT INTI MATAHARI - VIONAL FUTANTO (Management Department, Faculty of Economics and Business, Universitas Jambi, 2018)
Movement of the creative industry in Indonesia is growing rapidly, the public began to be interested to explore the creative industries. Inti matahari provides services such as the manufacture of residential parks, offices, public facilities, garden care and agricultural facilities targeting a segment of the people who are becoming aware of the importance of landscaping and wanting to spend more money on landscaping and orchard garden. The problems that arise in Inti Matahari is the difficulty to penetrate the market to new consumers and because the landscape industry is an industry that has a period of costumer in the manufacture of landscape, income gains are sometimes not sufficient to cover operating costs. To the authors want to do research where the authors want to see whether the consumer confidence, percept design quality, pecived capability of order, reputation already owned by Inti Matahari affect the purchase intention costumer interested interest in buying landscape and also the author wants to see how big the influence of price will play a role in repurchasing intention costumer, although costumer already interested in landscape design that given